Implementation decision support system in determining suppliers using wsm method - Mutiara; Nur yanti; Kamil Erwansyah; Badrul Anwar; Sri Kusnasari (Institute of Computer Science (IOCS), 2023)
Asia Sakti Foods Wahid Manufacturing is a company engaged in food production. For the sake of smooth production activities, the company needs suppliers, but in selecting suppliers, PT. Asia Sakti Foods Wahid Manufacturing still always gets suppliers who are less professional in their work, for example, delivery is not on time, prices are more expensive than market prices and so on, so things like this will have a negative impact on production continuity. The solution to the above problems is PT. Asia Sakti Foods Wahid Manufacturing requires a decision support system that can assist in making decisions on selecting new suppliers using the Weight Sum Model (WSM) method. It is hoped that this system can help overcome problems that exist in the company. The result of this system is a report supporting the decision of a new supplier who is eligible to become a permanent supplier at PT. Asia Sakti Foods Wahid Manufacturing. This report is expected to help reduce the error rate in selecting new suppliers.